2020
DOI: 10.15376/biores.15.2.2971-2993
|View full text |Cite
|
Sign up to set email alerts
|

The readiness of peninsular Malaysia wood-based industries for achieving sustainability

Abstract: Forests represent a substantial part of global socio-economy platforms. As the wood-based industry contributes large revenue to Malaysia’s economy, the readiness of Peninsular Malaysia towards sustainable wood-based industry was measured based on the different types of wood processing industries and Sustainable Forest Management (SFM) practice. Surveys (1,447) from all operating timber mills according to their raw materials type for wood products processing in Peninsular Malaysia were analyzed using multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In Indonesia, sustainability assessment in the furniture industry is limited to the manufacturing process [41]. Sustainability of the timber industry in West Malaysia was assessed by considering whether its forest management is sustainable or unsustainable in terms of raw material consumption status [42]. Feil et al [43] used a set of indicators on Medium Density Fiberboard (MDF) furniture manufacturing to assess the sustainability of the furniture industry, and the main findings showed that the construction of sustainability indicators was validated by a statistical methodology, which supported the consistency and quality of the sustainability evaluation of furniture companies.…”
Section: Evaluation Study On Recyclability Of Wooden Furniturementioning
confidence: 99%
“…In Indonesia, sustainability assessment in the furniture industry is limited to the manufacturing process [41]. Sustainability of the timber industry in West Malaysia was assessed by considering whether its forest management is sustainable or unsustainable in terms of raw material consumption status [42]. Feil et al [43] used a set of indicators on Medium Density Fiberboard (MDF) furniture manufacturing to assess the sustainability of the furniture industry, and the main findings showed that the construction of sustainability indicators was validated by a statistical methodology, which supported the consistency and quality of the sustainability evaluation of furniture companies.…”
Section: Evaluation Study On Recyclability Of Wooden Furniturementioning
confidence: 99%